The Minimisation of Combat Aircraft Life Cycle Cost through Conceptual Design Optimisation - Woodford, Spencer (Cranfield University, 1999)
In an effort to increase the cost-effectiveness of military equipment, a method has been developed to perform conceptual studies on combat aircraft, resulting in designs of specified capability optimised for minimum Life Cycle Cost (LCC). Consequently, the cost design loop can be considered as being closed, allowing the automated production of a consistent set of cost and performance data for different aircraft solutions. The design engineer can thus make informed, unbiased, design decisions, leading to a more efficient use of shrinking Defence budgets. Because of the vast scale to which the cost model could be developed, 'deep overheads' are not included, restricting the use of the tool to the comparison of similar weapons systems (combat aircraft), with a common set of design objectives and performance constraints. The aircraft conceptual design tool is based on classical design methods, recently adapted and updated, and validated with existing aircraft data. The engine performance and sizing modules have been developed from detailed thermodynamic models, whilst the LCC model is an amalgamation and update of several different methods, each written for a different phase in the system life cycle. The aircraft synthesis models, opfimisation tool and LCC algorithms are described, and validation results are presented where possible. The software cost model was used to generate a series of results, mimicking the early stages of an aircraft design selection procedure, and allowing a demonstration of the various trade-off studies that can be performed. Results from the selection process are presented and discussed, overall study conclusions arc drawn, and areas for further work suggested. Published data for real aircraft and engines are included in the Appendices, together with detailed aircraft parameter and cost output data generated by the model.